HIJAB DAN KEHORMATAN WANITA (STUDI ATAS DINAMIKA PERKEMBANGAN HIJAB DI KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA) - Ruqayyah, Ruqayyah; Veranita Indah, Astrid (Sulesana: Jurnal Wawasan Keislaman, 2026)
This study examines the dynamics of the development of hijab use and the meaning of women's honor values ​​in Sungai Kunjang District, Samarinda City. The hijab phenomenon among Muslim communities has undergone changes influenced by various factors, such as the level of religiosity, local culture, the role of social media, and the development of Muslim fashion trends. In this context, the hijab is not only understood as a religious obligation, but also functions as part of the lifestyle and forms the social identity of Muslim women. Based on this, this study focuses on two main problems, namely: (1) the development of hijab trends in Sungai Kunjang District, Samarinda City; and (2) the values ​​of women's honor in the development of hijab in the region. This study uses a descriptive qualitative approach. Data were obtained through observation, in-depth interviews, and documentation of Muslim women in Sungai Kunjang District who have diverse age and professional backgrounds. Research informants were determined purposively based on criteria that have been adjusted to the research focus. Data analysis was carried out in stages, including the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the development of hijab trends in Sungai Kunjang District has experienced quite significant dynamics. This is marked by the emergence of various modern hijab styles and models, heavily influenced by social media, public figures, and women's practical needs in their daily activities. Despite these changes in the form and style of hijab, most Muslim women continue to view the hijab as a symbol of honor, Islamic identity, and obedience to religious teachings. Its use also embodies sacred, social, vital, and material values.